2018
DOI: 10.1186/s13568-018-0675-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of quinoa (Chenopodium quinoa) fermented by Rhizopus oligosporus and its bioactive properties

Abstract: Quinoa is a pseudocereal that contains high quality protein, minerals, vitamins, polyphenols, and phytosterols. In this study, quinoa was fermented by Rhizopus oligosporus (R. oligosporus) up to 5 days and the functional compounds (l-carnitine, GABA, vanillic acid and gallic acid) were analyzed by LC/MS. The amounts of l-carnitine and GABA were 0.13 mg/kg and 540 mg/kg for nonfermented quinoa (NF), 3.15 mg/kg and 1040 mg/kg for fermented quinoa at 3 days (3F), and 1.54 mg/kg and 810 mg/kg for fermented quinoa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 27 publications
1
36
2
Order By: Relevance
“…However, quinoa phenolic fraction could inhibit the NO production stimulated by LPS in a concentration‐dependent manner. Hur et al (2018) found that the phenolics from fermented quinoa also showed a dose‐dependent effect on NO mediation of macrophages. In this study, at the concentration of 0.25 mg/ml, the groups of free and bound phenolic fractions from black quinoa showed significant ( p < .05) lower NO production values than those of the LPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, quinoa phenolic fraction could inhibit the NO production stimulated by LPS in a concentration‐dependent manner. Hur et al (2018) found that the phenolics from fermented quinoa also showed a dose‐dependent effect on NO mediation of macrophages. In this study, at the concentration of 0.25 mg/ml, the groups of free and bound phenolic fractions from black quinoa showed significant ( p < .05) lower NO production values than those of the LPS.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, quinoa is rich in functional nutrients such as phenolics. Phenolic compounds in quinoa are of great interest in recent years, since they contribute to reducing the chronic diseases by exhibiting antioxidant, anti‐inflammatory, and antitumor activities (Alvarez‐Jubete, Wijngaard, Arendt, & Gallagher, 2010; Carciochi, Galván‐D’Alessandro, Vandendriessche, & Chollet, 2016; Gawlik‐Dziki et al., 2013; Hur, Nguyen, Park, Kim, & Kim, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Rhizopus oligosporus (R. oligosporus), a fungus found predominantly in fermented soybean products such as Indonesian tempeh, hydrolyzes protein into amino acids and small peptides by various enzymes such as lipase, amylase, protease and glucoamylase, and synthesizes l-carnitine and γ-aminobutyric acid (GABA) in soybean, buckwheat and quinoa [25][26][27]. l-carnitine plays an important role in the transportation of fatty acids into the mitochondrial compartment for β-oxidation and subsequent energy production and antioxidant activity to prevent peroxidative damage [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…It also produces carbohydrate-cleaving enzymes such as β-glucosidase, β-glucuronidase and xylanase to create polyphenols from carbohydrates-conjugated phenolic compounds during fermentation [30,31]. R. oligosporus had been used to increase phenolic contents and antioxidant activities of soybean, buckwheat and quinoa through fermentation [27,32]. However, increased l-carnitine contents in fermented ginseng associated with biochemical characterization have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide production was determined as described previously [23]. RAW264.7 cells grown on a 96-well plate at 2 × 10 4 cells/well for 48 h were treated with FEPS at a concentration from 1.56-200 μg/ml with 1μg LPS/ml for 24 h and 100 μM indomethacin was used as a positive control.…”
Section: Measurement Of Nitric Oxide Productionmentioning
confidence: 99%